Epidemiological and clinical features of SARS-CoV-2 cluster infection in Anhui Province, Eastern China. (April 2022) - Wu, Jiabing; Chen, Xiuzhi; Gong, Lei; Huo, Shaohu; Gao, Xuehuan; Nie, Shuang; Chen, Fang; Hou, Sai; Song, Dandan; Ma, Wanwan; Jiang, Xuqin; Liu, Zhirong
Highlights: COVID-19 tends to be clustered. Severity of COVID-19 decreases between generations. Secondary attack rates decrease over time. Severely ill patients had a higher viral load. Abstract: Background: COVID-19 has spread worldwide and become a pandemic. We report the epidemiological and clinical characteristics of cluster infections. Methods: Data of clustered cases were retrieved from the public health emergency monitoring information system of China. We analyzed the incubation period, generation gap, secondary attack rate, and viral load in various grouped cases. Results: A total of 60 COVID-19 infection clusters including 226 patients and 19 asymptomatic cases involving four generations were analyzed. With the increase of transmission generations, secondary attack rate decreased ( P ＜0.001) and severity alleviated ( P  = 0.008). The median incubation period and intergenerational interval were 9 and 6 days, respectively. The secondary attack rate was 7.1% in the index cases, 5.0% in the first generation, 1.0% in the second generation, and 4.7% overall. Severe cases were seen more in the index (13, 65%) and first generation (7, 35%) ones, who had a significantly higher viral load than the mild and moderate ones. Conclusions: With the increase of transmission generation, secondary infection rate and severity decreased. Severe patients had a higher virus load. Patients in the incubation period and asymptomatic carriers were potential infection sources who might play an important role in transmission.